Perilaku hidup bersih dan sehat (tata cara pembuatan hand sanitizer) - Shinta Wulandari; Putri Wulan; Erick Bagas Pane; Ridho Akdhani Adzki; Diki Saputra (JOURNAL OF Public Health Concerns, 2023)
Background: Hand Sanitizer is a dosage form that can be used as an antiseptic. Hand Sanitizer is a hand sanitizer liquid that is used to kill germs on hands. Hand sanitizer contains an active ingredient of 96% alcohol. Alcohol is widely used as an antiseptic for the skin surface which serves to kill germs on the hands. With a hand sanitizer, it will make it easier for people to do activities outside the home. Purpose: Using H2O2 (Hydrogen Peroxide) as an antiseptic in the form of hand sanitizers and hand sanitizers is an alternative to prevent the spread of the covid-19 virus because it contains alcohol and other substances that can kill viruses that stick especially in the hand area. Method: 96% alcohol, geliserin, 3% hydrogen peroxide, then made into a liquid form in extra concentration and added with lemon essence. Results: The results of the preparation showed that all were homogeneous and white in color with the aroma of a mixture of lemon essence with a distinctive lemon aroma. The results of making antiseptic hand sanitizers got positive control. Counseling about PHBS and about the procedures for making hand sanitizers at SD N 01 Pinang Jaya went smoothly. Participants who were present were around 33 students in the first room and 29 students in the second room, by holding this counseling it is expected to increase knowledge of the quality of health for children to better maintain hand hygiene by using hand sanitizers to prevent transmission of the covid-19 virus. Conclusion: The conclusion that can be drawn from the description of community service activities (Elementary School) at SD N 01 Pinang Jaya, Pinang Jaya Kemiling is an increase in health knowledge to children about maintaining hand hygiene by using hand sanitizers.  Keywords: Hand Sanitizer; Antiseptic Spray As Hand Sanitizer; Counselling  Pendahuluan: Sediaan Hand Sanitizer merupakan bentuk sediaan yang dapat digunakan sebagai antiseptik. Hand Sanitizer adalah cairan pembersih tangan yang digunakan untuk membunuh kuman pada tangan. Hand sanitizer mengandung bahan aktif alkohol sebesar 96%. Alkohol banyak digunakan sebagai antiseptic untuk permukaan kulit yang berfungsi untuk membunuh kuman ditangan. Dengan adanya hand sanitizer akan memudahkan masyarakat pada saat melakukan aktivitas diluar rumah. Tujuan: MenggunakanH2O2 ( Hidroigen Peroxida ) sebagai antiseptik dalam bentuk hand sanitizer dan Hand sanitizer menjadi salah satu alternatif pencegahan menularnya virus covid-19 karena mengandung alkohol dan zat lain yang dapat membunuh virus yang menempel terutama di area tangan. Metode: Alkohol 96%, geliserin, hidrogen peroxsida 3%, kemudian dibuat menjadi bentuk cair dalam konsentrasi ektra dan di tambahkan lemonessen. Hasil: Hasil sediaan tersebut menunjukan bahwa semua homogen dan berwarna putih dengan aroma campuran lemonessen dengan aroma khas lemon. Hasil pembuatan antiseptik hand sanitizer mendapatkan kontrol positif.Penyuluhan tentang PHBS dan tentang tatacara pembuatan hand sanitizer di SD N 01 Pinang Jaya berjalan dengan lancar. Peserta yang hadir sekitar 33 siswa/i diruang pertama dan 29 siswa/I diruang kedua, dengan di adakan penyuluhan ini diharapkan dapat meningkatkan pengetahuan mutu kesehatan kepada anak-anak agar lebih menjaga kebersihan tangan dengan menggunakan hand sanitizer untuk mencegahan penularan virus covid-19 Simpulan: Kesimpulan yang dapat diambil dari uraian kegiatan pengabdian masyarakat (Sekolah Dasar) diSD N 01 Pinang Jaya, Pinang jaya Kemiling yaitu adanya peningkatan pengetahuankesehatan kepada anak-anak tentang menjaga kebersihan tangan dengan menggunakan hand sanitizer